2020
DOI: 10.1108/mip-08-2018-0319
|View full text |Cite
|
Sign up to set email alerts
|

UNGC principles and SDGs: perception and business implementation

Abstract: PurposeThe purpose of this study is to analyze the perception of CSR policies and the implementation of UNGC management model in firms operating at a national and an international level. Specifically, in the framework of stakeholder theory, this work explores the relation between internationalization and the usage of UNGC management model in the design and implementation of successful CSR strategies. By doing so, new insights on CSR management to gain competitive advantage are provided.Design/methodology/appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
3
17
0
1
Order By: Relevance
“…With regards to academia, the present study provides valuable insights to the TBL theory. Firstly, it has supported Albuquerque et al (2020)’s findings as well as tackling the gap identified by Mattera and Alba Ruiz-Morales (2020)’s study. In addition, the results obtained through this analysis complement the model established by Isaksson et al (2015) through a TBL framework.…”
Section: Conclusion Limitations and Future Lines Of Researchsupporting
confidence: 54%
See 2 more Smart Citations
“…With regards to academia, the present study provides valuable insights to the TBL theory. Firstly, it has supported Albuquerque et al (2020)’s findings as well as tackling the gap identified by Mattera and Alba Ruiz-Morales (2020)’s study. In addition, the results obtained through this analysis complement the model established by Isaksson et al (2015) through a TBL framework.…”
Section: Conclusion Limitations and Future Lines Of Researchsupporting
confidence: 54%
“…This study further deepens on the results obtained by Mattera and Alba Ruiz-Morales (2020) understanding the impact of UNGC management models in building sustainable business model in the long-term. The firms analysed show in the energy sector in Spain following the UNGC management model and having long term sustainable strategies can positively impact long-term financial performance and the ability to better manage a crisis.…”
Section: Conclusion Limitations and Future Lines Of Researchsupporting
confidence: 53%
See 1 more Smart Citation
“…The influence of the geographic scope: SDGs and multinational enterprises MNEs have a broad geographic scope, growth strategies, capabilities, degree of diversification, size, power and impact on the planet and society (Gupta and Govindarajan, 2000;Fleury and Fleury, 2011;Blowfield, 2012;Scheyvens et al, 2016;GapFrame, 2017;Muff et al, 2017;Ali et al, 2018;United Nations Global Compact, 2018;Van Zanten and Van Tulder, 2018;WBCSD, 2018;Mattera and Ruiz-Morales, 2020). The stakeholder pressure in MNEs in their home and subsidiary countries, and where they market their products and services.…”
Section: 4mentioning
confidence: 99%
“…The stakeholder pressure in MNEs in their home and subsidiary countries, and where they market their products and services. The argument is that MNEs suffer more pressure than enterprises doing business in only one country (North, 1990;Scheyvens et al, 2016;WBCSD, 2018;Lopez, 2020) what can lead them to consider global issues in strategies (Young and Tilley, 2006;Kramer and Porter, 2011;SDG Compass, 2016;Scheyvens et al, 2016;Van Zanten and Van Tulder, 2018;Mattera and Ruiz-Morales, 2020). Thus, a misdriven sustainability-oriented strategy would impose severe risks to their image and economic performance in a global dimension (MacLeod and Lewis, 2004;Scheyvens et al, 2016).…”
Section: 4mentioning
confidence: 99%